P155 Non-invasive ventilation (NIV) in acute hypercapnic respiratory failure in restrictive lung diseases (RLD). (16th November 2010) - Thomas, A; Ali, A; Chakraborty, B; Beauchamp, B; Gallagher, E; Banerjee, D; Mukherjee, R
Abstract : Introduction: Successful NIV has been described in RLD (thoracic cage disease, obesity-hypoventilation and neuromuscular diseases) and given the success in chronic ventilatory failure, NIV should be considered as the treatment of choice in decompensated ventilatory failure due to RLD in an acute setting. Methods: Analysis of initial ABG in those admitted to a NIV unit on a respiratory ward with a diagnosis of RLD, requiring NIV for an acute episode of respiratory failure (pH <7.35 and pCO2 >6.0 kPa) admitted between 01 August 2004 and 31 December 2009. Patients included were those with respiratory failure as a consequence of RLD. Those who were either admitted or managed in HDU were excluded from the analysis. The admission episodes were stratified by initial pH ranges (predictor variable) and in-hospital mortality was recorded (outcome variable). Results: In 270 admissions (221 unique patients) with RLD requiring NIV for acute respiratory failure, the overall mortality was 35 (13.0%). There was a significant increase in mortality in the group where ABG pH<7.15 (40.9%). The difference is significant when compared to the group with a pH between 7.15 and 7.26 (9.6%) (p=0.027). There was no significant difference in mortality in the group with pH 7.15 to 7.26 to the group with pH 7.26 to 7.35 (p=0.94): See Abstract P155 Figure 1 . The plot of fitted logistic regression equation with initial pH (the dotted lines indicate 95% confidence band). Conclusion: For those patients with RLD treated with NIV on a respiratory ward, the mortality increases with the severity of acidosis. As no current guidelines indicate a pH cut-off for the ward based management of RLD with NIV, from our results we propose that this could be an initial ABG pH of 7.15.